Memorial Objects in Small Interwar Lithuanian Towns as Manifestation of Citizenship - Smilingytė-Žeimienė, Skirmantė (Lietuvos istorijos studijos, 2025)
This research seeks to prove the hypothesis that the new monuments erected in smaller Lithuanian towns during the interwar years may be considered a generalized expression of setting up monuments throughout Lithuania, which would reveal the ongoing campaigns, promoted intentions, established dedications and would span across the spectrum of the nature of the monuments as well as their artistic quality. Residents of the smaller Lithuanian towns were able to unite for setting up monuments far more efficiently than urban residents. As a result, hundreds of monuments sprang up across the country during that timeframe. These new memorial objects – monuments and trees dedications – modified the public spaces of the small towns by transforming them into memory spaces and rendering them into the axis of new traditions. On the other hand, monuments were also a sign of the smaller towns becoming (more) Lithuanian. Smaller towns and their immediate environment were as if minor spaces of statehood: it was common to hoist the main national flag of the small town. Public monuments were as if inherent authenticity, they represented identity and became exceptional features of the locality. This point was reiterated during the Sąjūdis revival years, when the monuments were rebuilt en masse, and they became as if symbolic recreation of statehood at the site.
Keywords: public memorial objects; monuments; statehood; small towns; Lithuania in 1918–1940